2017
DOI: 10.1097/adm.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Post-Cesarean Section Opioid Analgesic Requirements in Women With Opioid Use Disorder Treated With Methadone or Buprenorphine

Abstract: Our study suggests that buprenorphine treatment will not interfere more than methadone with pain management after a cesarean section with no significant differences in opioid analgesic requirements, postoperative complications, or length of hospital stay. Future studies should investigate the generalizability to other surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…[2][3][4][5] Women with OUD are commonly excluded from prospective studies, and current knowledge rests on a few retrospective investigations of analgesic outcomes, but these reports lack anesthetic details relevant to pain after delivery. [6][7][8][9][10][11] Existing literature on perioperative handling of buprenorphine or methadone does not specifically discuss obstetrics. [12][13][14] Retrospective studies of postpartum analgesia in OUD populations usually relate analgesic regimens of oxycodone, non-steroidal anti-inflammatory drugs (NSAIDs), and acetaminophen with clinically practical, easily tracked analgesic outcomes such as verbal pain scores and daily opioid consumption (often standardized to oxycodone equivalents consumed).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Women with OUD are commonly excluded from prospective studies, and current knowledge rests on a few retrospective investigations of analgesic outcomes, but these reports lack anesthetic details relevant to pain after delivery. [6][7][8][9][10][11] Existing literature on perioperative handling of buprenorphine or methadone does not specifically discuss obstetrics. [12][13][14] Retrospective studies of postpartum analgesia in OUD populations usually relate analgesic regimens of oxycodone, non-steroidal anti-inflammatory drugs (NSAIDs), and acetaminophen with clinically practical, easily tracked analgesic outcomes such as verbal pain scores and daily opioid consumption (often standardized to oxycodone equivalents consumed).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Retrospective studies of postpartum analgesia in OUD populations usually relate analgesic regimens of oxycodone, non-steroidal anti-inflammatory drugs (NSAIDs), and acetaminophen with clinically practical, easily tracked analgesic outcomes such as verbal pain scores and daily opioid consumption (often standardized to oxycodone equivalents consumed). [6][7][8]10 In existing obstetric cohorts, the delivery method is often noted, but anesthetic details are not. [4][5][6][7][8][9][10] This study focuses on several analgesic outcomes: 24hour opioid requirements, pain scores, time to first postoperative pain medication received, delivery-to-discharge interval, intravenous (IV) patient-controlled analgesia (PCA) use, and truncal block use.…”
Section: Introductionmentioning
confidence: 99%
“…Because of buprenorphine's partial mu-opioid agonist properties, many providers worry about precipitating withdrawal or difficulty controlling pain by continuing a home regimen while a patient is in acute pain. Animal studies, human data, and experience have proven this incorrect and that a home buprenorphine regimen can be synergistic when given with opioids for acute pain 23,95. A recent study95 demonstrated baseline buprenorphine dosing does not interfere with opioid pain management after cesarean section and there is no statistically significant difference in postoperative complications nor length of hospital stay for patients taking full buprenorphine dosing when compared to those not taking buprenorphine.…”
Section: Labor and Delivery Pain Control Optionsmentioning
confidence: 99%
“…Animal studies, human data, and experience have proven this incorrect and that a home buprenorphine regimen can be synergistic when given with opioids for acute pain 23,95. A recent study95 demonstrated baseline buprenorphine dosing does not interfere with opioid pain management after cesarean section and there is no statistically significant difference in postoperative complications nor length of hospital stay for patients taking full buprenorphine dosing when compared to those not taking buprenorphine. Furthermore, discontinuing buprenorphine or reducing the dose exposes a new mother with OUD and the offspring to risks associated with withdrawal and maternal relapse and discomfort during a subsequent repeat induction.…”
Section: Labor and Delivery Pain Control Optionsmentioning
confidence: 99%
“…A study in 2017 compared post–cesarean section opioid analgesic pain requirements in women with opioid use disorder treated with methadone or buprenorphine. The study found no differences between groups in length of hospital stay, postoperative complications, or need for opioid analgesia [6].…”
mentioning
confidence: 99%